Atividade do sistema antioxidante e efeitos neurotóxicos em larvas de Rhamdia quelen em exposição aguda ao glifosato - Sobjak, Thaís Maylin (2016)
The advancement of agricultural techniques has enabled improvement and greater productivity, but also made the use of agrochemicals and inadequate in promoting exaggerated acute effects to non-target species. The pesticides are agents of greatest potential in degradation of aquatic environments, since, through the flood of agricultural areas, flowing organic or inorganic substances, natural or synthetic. Among the pesticides most used currently, include the non-selective herbicide glyphosate and organophosphorus compounds. To understand and prevent the damage caused to the environment, researchers have used multiple biomarkers as an effective tool for evaluation of environmental contamination. This study was divided into two studies: a manipulative experiment and other natural. The first study aimed to investigate the neurotoxic effects and about the system in larvae of Rhamdia quelen exposed to sublethal concentration of glyphosate. In this study it was possible to conclude that, in spite of the animals exposed to glyphosate having highest percentage of survival, there was an early induction of cholinesterase activity and antioxidant system, followed by the difficulty of maintaining the activities of antioxidant system in later times, resulting in a greater injury at the cellular level. The stress that animals suffer when they are exposed to the herbicide glyphosate causes a change in your metabolism being characteristic of elastic resistance. In the second study, the objective was to evaluate changes in antioxidant system and neurotoxic R. branneri present in streams with different levels of environmental contamination during autumn and winter. In this analysis, the response of biomarkers is related to the temporal variation, and possibly the exposure of these animals to pesticides. With the results obtained showed that the local biota responded differently in each season, signaling that the fauna is in contact with oxidizing agents and cholinesterasic in the period of autumn, when there is increased frequency of planting and use of pesticides